Differences that matter : feminist theory and postmodernism - Ahmed, Sara (Cambridge, UK ; New York : Cambridge University Press, 1998)
Differences That Matter challenges theories of the relationship between feminism and postmodernism that ask "is/should feminism be modern or postmodern?" Pointing out how postmodernism has been allowed to dictate feminist debates, Sara Ahmed argues instead that feminism must itself ask questions of postmodernism; that feminist theorists speak (back) to postmodernism rather than simply speak on (their relationship to) it. This "speaking back" involves a refusal to position postmodernism as a generalizable condition of the world, using close readings of postmodern constructions of rights, ethics, "woman," subjectivity, authorship and film.
Bibliografija: str. 204-213. - Kazalo
Keywords: Feminist theory; Postmodernism; feministička teorija; postmodernizam